2023
DOI: 10.1021/acsaelm.2c01390
|View full text |Cite
|
Sign up to set email alerts
|

Photogated Synaptic Transistors Based on the Heterostructure of 4H-SiC and Organic Semiconductors for Neuromorphic Ultraviolet Vision

Abstract: Neuromorphic vision that integrates the functionalities of sensing, memory, and processing may provide an important approach to overcome the drawbacks of a conventional artificial visual system such as data redundancy and high-power consumption. It has exhibited considerable potential to mimic the functionalities of human vision even beyond the visible-light range. In this work, we show an ultraviolet (UV)-responsive synaptic transistor based on the heterostructure of 4H-SiC and organic semiconductors. Benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Recently, the neuromorphic OFET device with heterostructure semiconductor materials has emerged, while single semiconductor material neuromorphic OFET devices always need a charge-storage layer or other functional layers between the insulating layer and channel layer. Noticeably, the heterostructure semiconductor materials always possess a heterointerface that promotes the separation of excitons [62][63][64][65][66][67][68][69][70][71][72][73][74]. Gao et al reported a P-type and N-type bulk heterostructure as the channel layer of the OFET device (figure 3(a)), which showed the different functions with different mixed ratios of N-type semiconductor to p-type materials [62].…”
Section: Heterojunction Semiconductor Materials In Ofetmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the neuromorphic OFET device with heterostructure semiconductor materials has emerged, while single semiconductor material neuromorphic OFET devices always need a charge-storage layer or other functional layers between the insulating layer and channel layer. Noticeably, the heterostructure semiconductor materials always possess a heterointerface that promotes the separation of excitons [62][63][64][65][66][67][68][69][70][71][72][73][74]. Gao et al reported a P-type and N-type bulk heterostructure as the channel layer of the OFET device (figure 3(a)), which showed the different functions with different mixed ratios of N-type semiconductor to p-type materials [62].…”
Section: Heterojunction Semiconductor Materials In Ofetmentioning
confidence: 99%
“…Additionally, several workers reported the neuromorphic OFET device with layer heterostructure semiconductors, for example, Liu et al depicted a synaptic transistor with the semiconductor material of 4H-SiC and organic semiconductors for neuromorphic ultraviolet (UV) vision [68]. In this device, the n-type 4H-SiC semiconductor material was selected as the substrate and light-sensitive layer of OFET, while the p-type P3HT organic material was used as the channel layer.…”
Section: Heterojunction Semiconductor Materials In Ofetmentioning
confidence: 99%
“…The negative photoconductance was used to optically demonstrate LTD of the device (Figure 1c) and synaptic image sensing of a handwritten digit which achieved 84% accuracy at its highest. A study by Liu et al in 2023 presented a photogated synaptic transistor for neuromorphic UV vision, using heterostructures of 4H-SiC and p-type organic semiconductors, including PVK and P3HT (Figure 1d) [81]. The main absorption of UV happens in the 4H-SiC layer, while PVK and P3HT serve as p-type channels due to their high hole mobility.…”
Section: Optoelectronic Neuromorphic Devices Using Uv Lightmentioning
confidence: 99%
“…Various synaptic functions, such as PPF and LTP, could be mimicked in this structure. Many synaptic devices have been investigated substantially and shown to mimic synaptic functions based on similar mechanisms [65][66][67][68]. It should be mentioned that charge-trap-flash-based synaptic transistors were successfully fabricated based on a silicon nitride film as the charge-trapping layer and a silicon film as the channel layer in transistor devices [69,70].…”
Section: Capture and Release Of Carriersmentioning
confidence: 99%